Patulin biodegradation using Pichia ohmeri and Saccharomyces cerevisiae - Coelho, A. R. [UNESP]; Celli, M. G. [UNESP]; Sataque Ono, E. Y.; Hoffmann, Fernando Leite [UNESP]; Pagnocca, Fernando Carlos [UNESP]; Garcia, S.; Sabino, M.; Harada, K. -I; Wosiacki, G.; Hirooka, E. Y. (Wageningen Acad Publ, 2008)
The effectiveness of Pichia ohmeri and Saccharomyces cerevisiae in the biodegradation of patulin was evaluated in vitro. Patulin is a toxin produced by Penicillium expansum, the predominant fungal contaminant in post-harvest apple. The biodegradation experiment was carried out in culture medium (Yeast Medium broth, YM) and commercial apple juice. These substrates were artificially contaminated with patulin previously produced by P expansum strain 2 in malt extract broth and purified over a silica gel column. The YM broth was inoculated with P. ohmeri 158 with proved anti-P expansum activity, whereas the apple juice was inoculated with dried Saccharomyces cerevisiae cells. The residual patulin in contaminated substrates was determined by reversed-phase HPLC. P ohmeri 158 in YM broth degraded over 83% of the initial 223 mu g (8.92 mu g/ml) of patulin after incubation at 25 degrees C for two days under static conditions; after five days of incubation, this percentage was greater than 99%, and patulin levels fell below the limit of detection after 15 days. In the apple juices inoculated with 0.25 g/l of commercial dried S. cerevisiae cells (corresponding 1.8 x 10(7) cells/till), 96% of patulin was degraded (initial contamination of 4.5 mu g/ml of patulin) after 143 hours of incubation at 25 degrees C under static conditions. However, 90% degradation occurred when the juice was contaminated with 7.0 mu g/ml under the same conditions, indicating that the biodegradation rate is concentration-dependent. The effective biodegradation of patulin using P ohmeri 158 and S. cerevisiae demonstrates a promising application for innocuous yeast isolated from natural microbiota in the biological control, which can prevent both fruit spoilage and P. expansum mycotoxin contamination.
Keywords: Penicillium expansum; antagonist yeasts; biocontrol; Patulin; degradation